Prosedur Pendaftaran Peralihan Hak atas Tanah secara Elektronik oleh Pejabat Pembuat Akta Tanah - Putri Rahmasari; Ichsan Anwary (Lembaga Yasin AlSys, 2026)
Although the role of Land Deed Officials (PPATs) in land registration has been widely studied, discussions specifically examining the procedures and legal force of electronic registration of transfers of land rights remain limited. This study aims to analyze the procedures and role of PPATs in the electronic registration of transfers of land rights and the legal force of the products generated through this process. This study employed a normative juridical method with statutory and conceptual approaches. Secondary data were collected through a literature review and analyzed qualitatively using prescriptive analysis. The findings show that PPATs are authorized to draw up authentic deeds concerning certain legal acts involving land rights through an electronic system and are responsible for verifying electronic certificates to ensure data conformity. Electronic certificates issued through an electronic system have legal force provided that the information contained therein can be accessed, displayed, and accounted for in accordance with Article 6 of the Electronic Information and Transactions Law. This study concludes that legal certainty in the electronic registration of transfers of land rights is determined by the exercise of PPATs’ authority, the reliability of the electronic system, and the conformity of the certificate issuance process with the provisions of laws and regulations. These findings contribute to the development of agrarian law and the law of evidence in the context of land administration digitalization. The practical implications emphasize the importance of strengthening the capacity of PPATs, harmonizing regulations, and improving the quality of services provided by the Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional to support the implementation of electronic land registration that ensures legal certainty.